X-ray transient absorption reveals the 1Au (nπ*) state of pyrazine in electronic relaxation - Valeriu Scutelnic (Nature Portfolio, 2021)
Radiationless relaxation is ubiquitous in natural processes and often involves excited states that are difficult to observe. Here the authors, combining X-ray transient absorption spectroscopy and computations, provide insight into the photoinduced dynamics in pyrazine and the involvement of an optically dark 1Au(nπ*) state.